Risk of hospitalization and death for healthcare workers with COVID-19 in nine European countries, January 2020–January 2021. (January 2022) - Ferland, L.; Carvalho, C.; Gomes Dias, J.; Lamb, F.; Adlhoch, C.; Suetens, C.; Beauté, J.; Kinross, P.; Plachouras, D.; Hannila-Handelberg, T.; Fabiani, M.; Riccardo, F.; et al.
Summary: This article presents and compares coronavirus disease 2019 attack rates for infection, hospitalization, intensive care unit (ICU) admission and death in healthcare workers (HCWs) and non-HCWs in nine European countries from 31 st January 2020 to 13 th January 2021. Adjusted attack rate ratios in HCWs (compared with non-HCWs) were 3.0 [95% confidence interval (CI) 2.2–4.0] for infection, 1.8 (95% CI 1.2–2.7) for hospitalization, 1.9 (95% CI 1.1–3.2) for ICU admission and 0.9 (95% CI 0.4–2.0) for death. Among hospitalized cases, the case-fatality ratio was 1.8% in HCWs and 8.2% in non-HCWs. Differences may be due to better/earlier access to treatment, differential underascertainment and the healthy worker effect.